1981
DOI: 10.3109/01485018108987536
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Autoradiography of Newly Formed Proteins in the Epididymis After Incorporation of Tritiated Amino Acids

Abstract: The synthesis and excretion of newly formed proteins in the principal cells of the head, body, and tail of the epididymis were studied by quantitative autoradiography in light and electron microscopy. Adult mice were killed from 5 min to 6 hr after intravenous injection of tritiated leucine, lysine, and arginine. The labels were taken up early and in greater amounts in the principal cells of the head. Radioactivity decreased in the cells of all three segments throughout the first hour following administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…At present, the principal cells are known to secrete certain compounds including glycoprotein or protein (LEA et al, 1978;OLSON and HAMILTON, 1978;FAYE et al, 1980;MOORE, 1980). The well developed rough endoplasmic reticulum and Golgi apparatus are interpreted as cytologic features concerned with the secretory activity (HoFFER et al, 1973;JONES et al, 1979;FAIN-MAUREL et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the principal cells are known to secrete certain compounds including glycoprotein or protein (LEA et al, 1978;OLSON and HAMILTON, 1978;FAYE et al, 1980;MOORE, 1980). The well developed rough endoplasmic reticulum and Golgi apparatus are interpreted as cytologic features concerned with the secretory activity (HoFFER et al, 1973;JONES et al, 1979;FAIN-MAUREL et al, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Although radioautographic studies have evidenced the pathway and kinetics of protein secretion in the various segments of the mouse epididymis (Fain-Maurel et al, 1981 ;Flickinger, 1981 ) (Brooks and Higgins, 1980) and the ram (Dacheux and Voglmayr, 1983) because of its expression in all the epididymal segments. The 30 Kd peptide most likely corresponds to the one previously designated CP 27 (27 Kd) (Flickinger etal., 1986) …”
Section: Introductionmentioning
confidence: 99%
“…The increase in the relative radioactivity concentration in RER from 2 to 15 min indicated that a large part of the newly formed proteins was accumulated in this organelle, as described in principal cells of the epididymis [3]. The observed peak in labeling of the Golgi apparatus at 30 min showed movement of synthetic product via this cell compartment.…”
Section: Discussionmentioning
confidence: 78%
“…Radioactivity was measured in the trichloroaceto-soluble fraction of the plasma and in the tissues from fixed and dehydrated fragments of epididymis as described in [ 3 ] . A radioactive pulse was reached between 2 and 10 rnin in the acid-soluble fraction of the plasma, whereas a radioactivity peak occurred in the tissue from 1 0 rnin on (95% of the radioactivity was in proteins).…”
Section: Methodsmentioning
confidence: 99%